Changing Mindset and Using of Language Game on Nawal Sa'dawi’s Al-Mar'ah wa al-Jins: A Perspective of Ludwig Wittgenstein - Arina Haque; Habil Abyad; Iffat Maimunah; Suo Yan Mei (Universitas Pendidikan Indonesia (UPI), 2022)
Each language has its own rules and pattern and a certain tendency. Language games are the rules of language for a particular purpose. Nawal Sa'dawi uses denotative meaning as criticism and disagreement about existing social phenomena. Therefore, this study aims to determine the form of language games in the book